Necessity of Big Data Security and its Relation to National Security - Adhikari, Sanjaya (Unity Journal, 2024)
Many government organizations like the Ministry of Home Affairs, the Department of Passport, Public Service Commission, Department of Transport Management, Election Commission of Nepal, hospitals, etc. are increasingly relying on data-centric services as the stored data helps to deliver the services effectively and efficiently. Such services are widespread due to increased internet usage, mobile devices, and network-based activities. The rapid expansion of technology usage has led to a corresponding shift in governance towards data-driven services. While adopting the data-driven services it brings forth a critical concern about the security and maintaining confidentiality of the citizens. The paper analyzes the existing policies, laws, and bylaws pertaining to data security and protection. It explores the challenges that exist for data security and protection. Furthermore, the paper identifies the necessity of big data security and its impact on national security due to data theft and breaches. The study has been undertaken by the use of secondary sources of information. While undertaking the research, the paper has delved into secondary sources; encompassing government policies, acts, regulations, reports and directives, international research articles, and views of cyber security experts. The paper has underscored the necessity of big data security measures and has identified the consequences that could be caused due to the inadequate security measures of the data as well as highlighted the importance of data privacy. The study contributes to the broader discourse on protecting data and its relation to national security.